2022
DOI: 10.1111/codi.16227
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of robotic resections for diverticular disease

Abstract: Aim: Resection of diverticular disease can be technically challenging. Tissue planes can be difficult to identify intraoperatively due to inflammation or fibrosis. Robotic surgery may improve identification of tissue planes and dissection which can facilitate difficult minimally invasive resections. This systematic review and meta-analysis evaluates the role of robotic surgery compared to laparoscopic surgery in diverticular resection. Methods:A systematic review and meta-analysis was performed in accordance w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 29 publications
(49 reference statements)
0
13
3
Order By: Relevance
“…The newer da Vinci Xi® was subsequently easier to dock and set up. In the systematic review by Larkins et al [9], operating time was longer with a robotic approach (p = 0.03) compared to laparoscopic approach [9]. Our study however demonstrated no signi cant difference in operating time in the laparoscopic and robotic anterior resection group (p = 0.095).…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…The newer da Vinci Xi® was subsequently easier to dock and set up. In the systematic review by Larkins et al [9], operating time was longer with a robotic approach (p = 0.03) compared to laparoscopic approach [9]. Our study however demonstrated no signi cant difference in operating time in the laparoscopic and robotic anterior resection group (p = 0.095).…”
Section: Discussioncontrasting
confidence: 60%
“…However, more current studies have demonstrated signi cant reductions in length of stay, conversion to open surgery rate, and hospital costs for surgeons performing a high volume of robotic surgery [4]. A recent systematic review of robotic resections in diverticular disease demonstrated that robotic surgery for diverticular disease was associated with a reduced conversion to open surgery, but a longer operating time as compared to laparoscopic surgery [9]. In another study comparing outcomes of robotic versus laparoscopic colorectal surgery for both benign and malignant conditions, performed by surgeons experienced in both robotic and laparoscopic procedures, they found no statistical difference in length of stay, time to return of bowel function, and time to discontinuation of patient-controlled analgesia [10].…”
Section: Discussionmentioning
confidence: 99%
“…Disease [1], and I congratulate the authors. However, I have some comments on the methodology used in this meta-analysis.…”
Section: Read With Interest the Meta-analysis About Robotic Resection...mentioning
confidence: 93%
“…The authors concluded that robotic surgery gives lower conversion (in all cases). They mentioned in the discussion section that 'The key findings from the data examined are that conversion rate is lower with a robotic approach while …' [1]. They considered that there was no heterogeneity.…”
Section: Read With Interest the Meta-analysis About Robotic Resection...mentioning
confidence: 99%
“…A recently published systematic review of colorectal resections for diverticular disease has shown a lower conversion rate in robotic surgery in comparison to laparoscopic surgery at the expense of longer operating time. 5 There is a paucity of data reporting on robotic resections for diverticular disease in Australasia. The aim of this current study is to report on safety and feasibility of robotic colorectal resection for diverticular disease in an Australian context.…”
Section: Introductionmentioning
confidence: 99%